KORELASI NILAI PROFITABILITAS PADA STRUKTUR MODAL - Biswan, Ali Tafriji; Subakti, Lidya Primta; Hidayat, Fikri (LAND JOURNAL, 2025)
This study aims to look at the impact of financial achievements or profitability on the capital structure of 80 companies listed on the IDX. The researcher used the purposive sampling method to determine the data analyzed in this study. The data taken is a company listed on the Indonesia Stock Exchange (IDX) which is included in the IDX 80. A search was carried out on the company on how it has performed in the last 3 years or from 2021 - 2023. The analysis tool used in this study is E-View 13. The results found by the researcher show that the Return on Asset variable is negatively correlated with Capital Structure. In contrast, Return on Equity is positively correlated with Capital Structure. On the other hand, simultaneously independent variables in this study had a significant effect. This research can focus on strategic management accounting theories. So that the results of this research can contribute to knowledge in strategic management accounting. This research focuses on IDX 80 data, in which there are companies that have high liquidity. But, research focuses on IDX 80 data, in which there are companies that have high liquidity